PERSPEKTIF PEMILIK PROYEK TERHADAP PERMASALAHAN DALAM MANAJEMEN KLAIM KONSTRUKSI - Fatena Rostiyanti, Susy; Hansen, Seng (JURNAL SPEKTRAN, 2017)
The uncertainty and complexity of construction projects often result in conflicts and unavoidable claims. Commonly, claims are submitted by the contractor for additional payment or time extensions triggered by the additional works beyond general terms and contract conditions. Unsuitable claims may lead to disputes so there is a need for claims management to avoid potential disputes. Claims can not be avoided in any construction project, but a properly executed management approach is expected to reduce the impact of claim that leads to disputes. Evaluation to problems in the six stages of claims management was conducted through questionnaires distribution to project owner and analyzing using significance index approach. The problems that often arise in each phase are elaborated in a form of Likert question. The results of field data collection are processed to obtain the most significant problems arisen in each claim management phase. The results indicate that from the six phases of claims management, the problems that often arise are related to four aspects, namely the availability of standard in claims management, the availability of competent human resources handling claims, the limitation of communication ability, and the limited ability to document the implementation of the project.   Keywords: claims management , owner , contruction project , significance index